SLEEVE GASTRECTOMY AND FUNDOPLICATION AS A SINGLE PROCEDURE IN PATIENTS WITH OBESITY AND GASTROESOPHAGEAL REFLUX - LASNIBAT,Juan Pablo (2017)
ABSTRACT Background: Bariatric surgery in Chile has seen an exponential increase in recent years, especially in sleeve gastrectomy. Its use is currently discussed in patients suffering from gastroesophageal reflux disease. Different options have been considered for the management of these patients but up to now laparoscopic Roux-en-Y gastric bypass seems to be the best option. Sleeve gastrectomy plus concomitant fundoplication or hiatal hernia repair also has been suggested in patients having reflux or small hiatal hernia. Aim: To present a cohort of obese patients with gatroesophageal reflux undergoing this procedure, which seeks to provide the benefits of both laparoscopic gastric sleeve (LSG) and antireflux surgery focused on the evaluation of presence of reflux and BMI after surgery, and to compare the result observed in this cohort with a previous group of obese patients without reflux submitted to sleeve gastrectomy alone. Methods: Retrospective case series in 15 patients who underwent this surgery between the years 2003 and 2012. Clinical records were analyzed and values ​​of 24 hr pH monitoring, esophageal manometry and clinical outcome were recorded. Results were compared to a previous series of patients who underwent LSG. No statistical analyses were made. Results: Group A consisted of 15 patients submitted to LSG plus fundoplication. 93% (n=14) were female. Mean age was 46.2 years. Mean preoperative body mass index (BMI) was 33.9. All patients had altered pH monitoring and manometry preoperatively. There was one minor complication corresponding to a seroma. There was no perioperative mortality. Group B consisted of 23 obese patients who underwent LSG. These patients developed de novo reflux, hypotensive LES and esophagitis after the surgery. Group A patients showed improvement in esophageal pH monitoring and manometry at three months. During long-term follow-up, six underwent revision surgery, four for weight regain, one regained weight associated with symptomatic reflux, and one underwent re-intervention for reflux. Conclusions: Good results are observed in the short-term follow up in both reflux resolution and weight loss. Nevertheless, results at long term are discouraging, with 53.3% of the patients requiring revision surgery during follow-up.